Analisis Pengendalian Kualitas Menggunakan Metode Seven Tools dan FMEA pada Proses Printing - Aditya Fahrizal Kurniawan; Siti Muhimatul Khoiroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT XYZ is a packaging printing company facing quality problems due to a high defect rate in its printing process. This study aims to identify dominant defects, determine the root causes of defects, and develop improvement recommendations to enhance product quality. The methods employed were Seven Tools consisting of check sheets, stratification, histograms, Pareto diagrams, p-control charts, and fishbone diagrams, combined with Failure Mode and Effects Analysis (FMEA) and the 5W+1H approach. The results showed that total defects during July–December 2025 reached 4,320,066 units out of 166,435,973 units produced. The dominant defects were out-of-range color defects (38.39%), dirty printing defects (31.06%), and incorrect design code placement (18.75%), contributing 88.14% of total defects. The p-control chart indicated that the process was not statistically controlled because several observations exceeded the control limits. Improvement recommendations include implementing boundary samples, standardized ink mixing procedures, first product inspection, visual marking, and visual cleaning SOPs to reduce defect levels and improve printing quality.